2013
DOI: 10.1021/cs400495j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, Stable, and Reusable Silicoaluminophosphate for the One-Pot Production of Furfural from Hemicellulose

Abstract: Development of stable, reusable, and water-tolerant solid acid catalysts in the conversion of polysaccharides to give value-added chemicals is vital because catalysts are prone to undergo morphological changes during the reactions. With the anticipation that silicoaluminophosphate (SAPO) catalysts will have higher hydrothermal stability, those were synthesized, characterized, and employed in a one-pot conversion of hemicellulose. SAPO-44 catalyst at 170 °C within 8 h could give 63% furfural yield with 88% mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…Upon working with monosaccharides, observations were made that to achieve the maximum furfural yield, a water/organic solvent biphasic system is better than only water or only organic solvent . With regard to the limited solubility of sugars and furfural in various solvents (which can form biphasic solvent systems); in a recent study, after calculating the partition coefficient and checking the miscibility of organic solvents in water, it was demonstrated that the water/toluene system yields the highest amount of furfural in a batch‐mode reaction compared to water/ p ‐xylene and water/methyl iso ‐butyl ketone (MIBK) . Although, a range of solid acids are known for the synthesis of furfural from xylose, it becomes indispensable to first obtain xylose from the hemicellulose/xylan part (polysaccharide) of naturally abundant lignocellulose .…”
Section: Introductionsupporting
confidence: 62%
“…Upon working with monosaccharides, observations were made that to achieve the maximum furfural yield, a water/organic solvent biphasic system is better than only water or only organic solvent . With regard to the limited solubility of sugars and furfural in various solvents (which can form biphasic solvent systems); in a recent study, after calculating the partition coefficient and checking the miscibility of organic solvents in water, it was demonstrated that the water/toluene system yields the highest amount of furfural in a batch‐mode reaction compared to water/ p ‐xylene and water/methyl iso ‐butyl ketone (MIBK) . Although, a range of solid acids are known for the synthesis of furfural from xylose, it becomes indispensable to first obtain xylose from the hemicellulose/xylan part (polysaccharide) of naturally abundant lignocellulose .…”
Section: Introductionsupporting
confidence: 62%
“…As observed in Table , Cu 0.1 ‐SAPO‐44 experienced a significant surface area and pore volume loss after ion‐exchange treatment. SEM images of SAPO‐44 show cubic‐like rhombohedral morphology (Figure S2, in the Supporting Information), quite similar to those in the literature . After Cu ion exchange, the morphology of Cu 0.1 ‐SAPO‐44 was nearly identical to that of the parent SAPO‐44 except for some irregular fragments, in agreement with the decrease of crystallinity as revealed by XRD (Figure ).…”
Section: Resultsmentioning
confidence: 96%
“…Unfortunately, a very poor yield of furfural was obtained using xylan without any pretreatment, although a high yield (67%) was achieved for xylose ( Table 3, entries 6 and 7). 30 Note that they used xylan obtained from the same source as we used. The hemicellulose structure of xylan could not be decomposed under such mild conditions.…”
Section: Conversion Of Polysaccharidesmentioning
confidence: 99%